Costs in Alternative Locations: The Radio Industry. - Hague, D. C.; Dunning, J. H. (Review of Economic Studies, 1954)
D. C. Hague, J. H. Dunning; Costs in Alternative Locations: The Radio Industry, The Review of Economic Studies, Volume 22, Issue 3, 1 January 1954, Pages 2